Nonconforming Elements in the Mixed Finite Element Method (Journal of Computational Mathematics, 1984)
In this paper, an abstract error estimate of mixed finite element methods using nonconforming elements is presented. In addition, a class of nonconforming rectangular elements is proposed, and applied to Stokes equations. The optimal error estimate is given.